Correlation Between Heart Rate Characteristic Index Score and Severity of Brain Injury in Neonates With Hypoxic-Ischemic Encephalopathy. (August 2020) - Kayton, Allyson; DeGrazia, Michele; Sharpe, Elizabeth; Smith, Denise; Perez, Jose A.; Weiss, Michael D.
Abstract : Background: Hypoxic-ischemic encephalopathy (HIE) remains devastating for neonates despite widespread treatment with therapeutic hypothermia (TH). The heart rate characteristic (HRC) index score, a measure of heart rate variability, could prove useful in the management of neonates with HIE as new therapies emerge or when withdrawal-of-support decisions are being considered. Purpose: The main purpose was to describe correlation between HRC index scores and brain magnetic resonance imaging (MRI) severity of injury for neonates with HIE. Methods/Analysis: Low/high HRC index scores retrieved at initiation of TH (baseline), 24, 48, 72, and 96 hours, brain MRI severity of injury, and National Institute of Child Health and Human Development Death/Disability and Death scores were collected and analyzed retrospectively. Independent t tests and linear regression were used to examine relationships for each outcome measure. Results: Twenty-seven neonates were stratified into 2 groups: noninjury (n = 11) and injury (n = 16). Statistically significant relationships were observed. Strikingly, mean low HRC index score for the noninjury group ranged between 0.37 and 0.65 and was between 0.61 and 0.86 for the injury group. Mean high HRC index score for the noninjury group ranged between 0.66 and 1.02 and was between 1.04 and 1.41 for the injury group. Implications for Practice: HRC index score may be a useful guide in the future management of neonates with HIE. Implications for Research: This study established correlations between HRC index and MRI injury scores in neonates treated with TH. Further research is warranted to establish important relationships between brain injury and HRC index scores before this tool can be used clinically for this purpose.